2013
DOI: 10.1111/apa.12149
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat accumulation and metabolic syndrome in children: the impact of Trp64Arg polymorphism of the beta3‐adrenergic receptor gene

Abstract: Trp64Arg polymorphism of the ADRB3 gene may affect VF accumulation and be associated with MS, a cluster of conditions involving aggravated lipid metabolism and higher blood pressure, in Japanese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…This inversion explains ∼40% of the population-attributable risk for joint susceptibility to obesity and asthma. Additional genes including the β2-adrenergic receptor gene (ADRB2), 148,149 the TNF gene, 150,151 and the lymphotoxin-α (LTA) gene 152,153 have been associated in both obesity and asthma in children. However, the limited number of these studies highlights the paucity of data on genetic susceptibility for obesity-related asthma.…”
Section: Genetics Of Obesity-related Asthmamentioning
confidence: 99%
“…This inversion explains ∼40% of the population-attributable risk for joint susceptibility to obesity and asthma. Additional genes including the β2-adrenergic receptor gene (ADRB2), 148,149 the TNF gene, 150,151 and the lymphotoxin-α (LTA) gene 152,153 have been associated in both obesity and asthma in children. However, the limited number of these studies highlights the paucity of data on genetic susceptibility for obesity-related asthma.…”
Section: Genetics Of Obesity-related Asthmamentioning
confidence: 99%
“…Unfortunately, a number of factors make intervention studies difficult to compare: differences in dietary changes (caused both by recommendations and patient compliance); the intensity and frequency of physical activity; the pre-selection of participants; and the relatively low number of individuals included (often less than 100 participants). Therefore, it is not surprising that most of the studies published to date have recorded inconclusive results and are difficult to replicate (8)(9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…In the coding region of this AR subtype a common missense mutation resulting in the substitution of arginine for tryptophan at codon 64 (Trp64Arg) has been reported to be significantly associated with whole body obesity, visceral fat accumulation and other metabolic syndrome components or their cluster [54][55][56][57]. Unfortunately, as previously observed in adults' studies, the association between Trp64Arg and BP levels in obese children was found significant in some studies [54,58] and not significant in others [51,53]. The inconsistencies between these different children's populations have led some investigators to conclude that the Trp64Arg variant plays a small role in human obesity and its related conditions such as hypertension [53].…”
Section: α-And β-Adrenergic Receptors (Adra and Adrb) Genesmentioning
confidence: 98%